Novel somatic alterations in unicentric and idiopathic multicentric Castleman disease. (21st September 2021) - Goodman, Aaron M.; Jeong, Ah‐Reum; Phillips, Alexis; Wang, Huan‐You; Sokol, Ethan S.; Cohen, Philip R.; Sicklick, Jason; Fajgenbaum, David C.; Kurzrock, Razelle
Abstract: Objectives: Castleman disease (CD) is a heterogeneous group of disorders involving systemic inflammation and lymphoproliferation. Recently, clonal mutations have been identified in unicentric CD (UCD) and idiopathic multicentric CD (iMCD), suggesting a potential underlying neoplastic process. Methods: Patients with UCD or iMCD with next generation sequencing (NGS) data on tissue DNA and/or circulating tumor DNA (ctDNA) were included. Results: Five patients were included, 4 with iMCD and 1 with UCD. Four patients (80%) were women; median age was 40 years. Three of five patients (60%) had ≥1 clonal mutation detected on biopsy among the genes included in the panel. One patient with iMCD had a 14q32‐1p35 rearrangement and a der(1)dup(1)(q42q21)del(1)(q42) (1q21 being IL‐6R locus) on karyotype. This patient also had a NF1 K2459fs alteration on ctDNA (0.3%). Another patient with iMCD had a KDM5C Q836* mutation, and one patient with UCD had a TNS3‐ALK fusion but no ALK expression by immunohistochemistry. Conclusions: We report 4 novel somatic alterations found in patients with UCD or iMCD. The 1q21 locus contains IL‐6R, and duplication of this locus may increase IL‐6 expression. These findings suggest that a clonal process may be responsible for the inflammatory phenotype in some patients with UCD and iMCD.